Systematic Approach to Ecopedagogical Conceptual Principles in Continuous Ecological Education - Shermatova Uljamol; Jumayeva Oysanam Anvarovna (International Journal on Integrated Education, 2022)
The article introduces future teachers to continuous ecological education, pedagogical conceptual professional and personal qualities, educational process, ecological culture, use of funds, educational process, creativity created by students, science education educational and methodological complex, systematic study of ecological, legal, political, economic, philosophical, pedagogical, technical-technological, aesthetic and moral aspects of a person is reflected.